Allelopathic Influence of a Wheat or Rye Cover Crop on Growth and Yield of No‐Till Cotton. (1st November 2013) - Li, Yue; Allen, V. G.; Chen, J.; Hou, F.; Brown, C. P.; Green, P.
Abstract : No‐till planting cotton ( Gossypium hirsutum L.) into small grain cover crops has many benefits including allelopathic suppression of weeds but potential to also suppress cotton has been suggested. We investigated effects of rye ( Secale cereal L.), wheat ( Triticum aestivum L.), or no cover crop on no‐till planted cotton in a 3‐yr field‐plot experiment (randomized block design; 4 blocks), conducted at the Texas Tech Field Laboratory, New Deal. Soil was Pullman clay loam (fine, mixed, superactive, thermic Torrertic Paleustolls). From 2007 to 2009, wheat or rye was planted into one‐half of each replicate plot each September. Growth, removed in May, was chemically terminated with glyphosate. Cultivar FiberMax 9058F cotton was no‐till planted each May and was harvested by December. By the end of the growing season, cotton planted with no cover crop was taller ( P < 0.05) than cotton planted into cover crops. Cotton lint and seed yield were reduced ( P < 0.05) by cover crops but the magnitude of the effects differed each year. Cotton leaf chlorophyll, measured in September 2009, was greater ( P < 0.05) when no cover crop was used than for cotton planted into cover crops. Higher ( P < 0.05) concentrations of three allelochemicals [2, 4‐dihydroxy‐7‐methoxy‐(2 H )‐1, 4‐benzoxazin‐3(4 H )‐one (DIMBOA); 2, 4‐dihydroxy‐(2 H ) ‐1, 4‐benzoxazin‐3 (4 H )‐one (DIBOA); 2‐benzoxazolinone (BOA)] were detected in soils where cover crops grew than where no cover crops were used but amounts varied due to specific cover crop and sampling date. Results suggest that lower cotton growth and yield due to cover crop may be partly due to their release of allelochemicals.